Development of Augmented Reality Flashcard Media to Improve the Ability of Grade IV Elementary School Students in Reading Understanding of Alternative Energy Source Materials - Novi Listiyani; Sholeh Hidayat; Lukman Nulhakim (Jurnal Penelitian Pendidikan IPA, 2021)
The use of information and communication technology such as social media has become a necessity as well as a demand in the global era. Therefore, it is necessary to develop various creative and innovative educational models so that the educational process does not seem less interesting, monotonous, and boring so that it will limit the formation of the transfer of knowledge, which is the focus of research. The purpose of this research is how appropriate the development of augmented reality flashcard media is to improve the ability of fourth grade elementary school students to read comprehension of alternative energy source materials. This research uses the Research and Development (R&D) method with the ADDIE development model. The results obtained are that this development research creates a product in the form of an augmented reality flashcard media which is designed as an android-based application. In the feasibility test, the validation results of the material experts reached an average percentage of 85%, which indicated very good qualifications. The validation results of media experts with an average percentage of 78%, which indicated good qualifications.